2019
DOI: 10.12911/22998993/99787
|View full text |Cite
|
Sign up to set email alerts
|

Research of Effective Microorganisms on Dairy Sewage Sludge Stabilization

Abstract: The present paper was aimed at determining the influence of particular methods and biological processes, including the application of Effective Microorganisms, on the change in characteristics of the treated dairy sewage sludge, especially when discussing the changes in the content of nutrients and macroelements. The purpose of the conducted research was to specify the possibility of using natural biological methods of dairy sewage sludge treatment and adapting it to environmental, especially farming use. Diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Wastewater sediments and organic fractions of municipal solid wastes are even less favorable for Eisenia Fetida. However, being mixed with manure in an optimal proportion, they are also suitable for bioconversion and biocompost production complying with environment safety requirements [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Wastewater sediments and organic fractions of municipal solid wastes are even less favorable for Eisenia Fetida. However, being mixed with manure in an optimal proportion, they are also suitable for bioconversion and biocompost production complying with environment safety requirements [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…For example, there is an experience of successful processing of wastewater mud of paper manufacture when they are mixed with the biowaste of cattle in a proportion of 50-75% with cultivation in the substrate of the worms population Eisenia fetida and fungus Oligoporus placenta [16]. Worms also most effectively apply themselves in symbiosis with effective microorganisms in the processing of dairy waste [17]. Also, the vermiculture use in bioconversion of wastewater mud significantly reduces the emission of associated greenhouse gases [18].…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to their use, it is possible, for example, to reduce sludge volume and shorten aeration time (Grabas et al 2016 ; Safwat 2018 ), as well as to reduce odor emissions from waste and support its humification (Fan et al 2018 ). Studies also found reduced nutrients and organic matter content when treating dairy wastewater (Boruszko 2019 ). In addition, the application of EM contributed to the improvement of vegetable production in agriculture (Olle and Williams 2015 ).…”
Section: Introductionmentioning
confidence: 99%